2002
DOI: 10.1007/s00428-001-0598-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistomorphologic and molecular cytogenetic analysis of a carcinosarcoma of the urinary bladder

Abstract: Carcinosarcomas of the urinary bladder are malignant biphasic tumors with an epithelial and a spindle cell component. For the histogenesis of the two components, a biclonal and a monoclonal origin are discussed. We present the immunomorphology and molecular cytogenetics of such a case. The immunohistology of biopsies of the urinary bladder revealed a poorly differentiated urothelial carcinoma (GIII) and a co-existing pleomorphic, spindle cell leiomyosarcoma (GIII). The two components were microdissected and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 14 publications
2
26
0
2
Order By: Relevance
“…22 More recently, concordant X-chromosome inactivation and significant overlap in loss of heterozygosity were reported in separately microdissected components of sarcomatoid carcinoma of the urinary bladder in a study by Sung et al, 23 supporting a monoclonal origin for both components. Gronau et al 24 obtained similar results, finding that the tumor components showed overlapping chromosomal alterations as well as additional nonoverlapping alterations. These secondary mutational aberrations were thought to represent events significant in the divergence occurring after the initial tumorigenesis.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…22 More recently, concordant X-chromosome inactivation and significant overlap in loss of heterozygosity were reported in separately microdissected components of sarcomatoid carcinoma of the urinary bladder in a study by Sung et al, 23 supporting a monoclonal origin for both components. Gronau et al 24 obtained similar results, finding that the tumor components showed overlapping chromosomal alterations as well as additional nonoverlapping alterations. These secondary mutational aberrations were thought to represent events significant in the divergence occurring after the initial tumorigenesis.…”
Section: Discussionmentioning
confidence: 71%
“…These secondary mutational aberrations were thought to represent events significant in the divergence occurring after the initial tumorigenesis. 24 Although TP53 mutations are common in urothelial carcinomas, particularly in high-grade and highstage cancers, TP53 mutation analysis has not previously been utilized to evaluate the molecular characteristics of the morphologically distinct components of sarcomatoid carcinoma of the urinary bladder. TP53 exons 5-8, corresponding to the DNAbinding domain, are considered to be the region most frequently harboring point mutations in bladder carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,[13][14][15]17,19,22 In different anatomical sites, most, but not all, of these tumors composed of carcinoma and sarcoma or sarcoma-like components are considered monoclonal growths (the so-called divergent hypothesis) rather than true collision tumors (convergent hypothesis). 20,[23][24][25][26][27][28][29][30][31] In turn, these monoclonal growths may originate from a single ancestor undergoing divergent epithelial and mesenchymal differentiation early during the neoplastic transformation (combination theory), or the full-blown carcinoma cells undergo sarcomatoid changes during tumor progression (conversion theory). 21,[23][24][25] In the lung, a monoclonal origin has been suggested for carcinosarcoma and blastoma using diverse molecular strategies, such as X chromosome inactivation, 24 microsatellite analysis, 29 and mutational genotyping of p53 gene, 28 whereas little is known about clonality of pulmonary pleomorphic carcinomas.…”
mentioning
confidence: 99%
“…They usually present as well-circumscribed grayish firm nodules. 5 Bladder leiomyosarcoma has always been considered a highly aggressive tumour. Most patients are already in the advanced pathologic stage when the tumour is detected; less than 15% of tumours are identified in the T1 stage.…”
Section: Discussionmentioning
confidence: 99%